2014
DOI: 10.4103/0028-3886.149391
|View full text |Cite
|
Sign up to set email alerts
|

Co-morbidity of depression and epilepsy in Jimma University specialized hospital, Southwest Ethiopia

Abstract: In this study, depression was found to be highly prevalent. Early recognition and treatment of depression through routine screening and assessment of PWE should become an essential part of diagnosis and treatment protocol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
20
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 22 publications
5
20
1
Order By: Relevance
“…People who had side effects of medication and frequent seizure were found to have depression and anxiety as compared to people who had no side effects of medication and no seizure. This finding was consistent with many previous studies [ 9 , 24 ].…”
Section: Discussionsupporting
confidence: 94%
“…People who had side effects of medication and frequent seizure were found to have depression and anxiety as compared to people who had no side effects of medication and no seizure. This finding was consistent with many previous studies [ 9 , 24 ].…”
Section: Discussionsupporting
confidence: 94%
“…This is evidenced in the previous community-based study in Ethiopia showed that providing a high level of psychological support protect the individuals from developing common mental illness by 50% [47]. Frequent seizure attacks were associated with common mental illness which is consistent with other studies [48][49][50][51]. Many epilepsy patients become fearful when they have seizure attacks in public place: one of the most awful things for epilepsy patients, felt ashamed about their unpredictable seizure attacks may be associated with socially unaccepted sign like incontinence of feces, urine, jerking movements, bite of tongue or cheek may occur and bloody saliva may come from the mouth.…”
Section: Discussionsupporting
confidence: 89%
“…The prevalence of depression among PWE in this resource limited setting using the primary care validated cut-off (70.8%) was also higher than the general population depression prevalence (28.8%) using the same validated cut-off (5 or more) [38]. This prevalence of depression was also higher than the prevalence that is reported in the institution based studies from Ethiopia [79]. Various explanations have been proposed to explain the elevated levels of depression in epilepsy; (1) underlying structural brain disease, (2) damage related to uncontrolled seizures, and (3) psychosocial impact of the stigma and disability associated with epilepsy [6].…”
Section: Discussionmentioning
confidence: 73%
“…Hospital based studies conducted in Ethiopia have shown that the prevalence of depression is high among people with epilepsy [79]. Comorbid psychiatric disorders, such as depression, have a substantial negative impact on quality of life [1012] and are important risk factors for suicidal behaviours [13].…”
Section: Introductionmentioning
confidence: 99%